Early palliative home care: Evaluation of an interprofessional educational intervention for district nurses and general practitioners about nutritional care. (16th August 2017) - Berggren, Erika; Ödlund Olin, Ann; Orrevall, Ylva; Strang, Peter; Johansson, Sven-Erik; Törnkvist, Lena
Background: Teamwork is important in early palliative home care, and interprofessional education is required to achieve teamwork. It is thus crucial to ensure that interprofessional education works well for the members of all participating professions because levels of knowledge and educational needs may vary. Aim: To evaluate, by profession, the effectiveness of an interprofessional educational intervention for district nurses and general practitioners on three areas of nutritional care for patients in a palliative phase. Design: A quasi-experimental study that used a computer-based, study-specific questionnaire to evaluate the effectiveness of the intervention. The continuing education in primary health care (ConPrim ® ) model was used to create the intervention. ConPrim includes a web-based program, a practical exercise and a case seminar, all with interprofessional training. Setting: Primary health care centers in Stockholm County, Sweden. Intervention group (n = 87; 48 district nurses, 39 general practitioners); control group (n = 53; 36 district nurses, 17 general practitioners). Results: The total intervention effect was significant in all three areas, p = 0.000–0.004. The intervention effects were similar and significant for both professions in areas 1 and 2. In area 3, the intervention effects were significant for general practitioners but not for district nurses. Conclusions: The intervention seems promising, as it may create better prerequisites for teamwork and caring for patients living at home. However, it needs to be optimized to better increase district nurses' level of knowledge (area 3).